Low temperatures reduce skin healing in the Jacare do Pantanal (Caiman yacare, Daudin 1802) - Pressinotti, Leandro Nogueira; Borges, Ricardo Moraes; Alves de Lima, Angela Paula; Aleixo, Victor Manuel; Iunes, Renata Stecca; Shimada Borges, Joao Carlos [UNESP]; Cogliati, Bruno; Machado Cunha da Silva, Jose Roberto (Company Biologists Ltd, 2013)
Studies of skin wound healing in crocodilians are necessary given the frequent occurrence of cannibalism in intensive farming systems. Air temperature affects tissue recovery because crocodilians are ectothermic. Therefore, the kinetics of skin wound healing in Caiman yacare were examined at temperatures of 33 degrees C and 23 degrees C. Sixteen caiman were selected and divided into two groups of eight maintained at 23 degrees C or 33 degrees C. The studied individuals' scars were photographed after 1, 2, 3, 7, 15 and 30 days of the experimental conditions, and samples were collected for histological processing after 3, 7, 15 and 30 days. Macroscopically, the blood clot (heterophilic granuloma) noticeably remained in place covering the wound longer for the caiman kept at 23 degrees C. Microscopically, the temperature of 23 degrees C slowed epidermal migration and skin repair. Comparatively, new blood vessels, labeled using von Willebrand factor (vWF) antibody staining, were more frequently found in the scars of the 33 degrees C group. The collagen fibers in the dermis were denser in the 33 degrees C treatment. Considering the delayed healing at 23 degrees C, producers are recommended to keep wounded animals at 33 degrees C, especially when tanks are cold, to enable rapid wound closure and better repair of collagen fibers because such lesions tend to compromise the use of their skin as leather. (C) 2013. Published by The Company of Biologists Ltd. This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution and reproduction in any medium provided that the original work is properly attributed.
Keywords: Crocodilians; Inflammation; Histology